To Determine Frequency and Outcome of Dyslipidemia in Diabetic Foot Patients - Farheen Khadim, Kashif Ali Samin, Muhammad Usman Sajid, Shazia yousaf, Jahangir Anjum, Saba Shafiq, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine frequency and outcome of Dyslipidemia in Diabetic foot patient Study Design: Cross sectional study Place and Duration: Divisional Head Quarter Teaching (DHQ) Hospital Mirpur AJK from January 2021 to January 2022. Methodology: This study includes one hundred and thirty nine (139) patients with Type 2 diabetes and diabetic foot related complication. Patient diagnosed case of type2 DM on oral hypoglycemic agents or on insulin therapy of age >30 of either gender admitted with history of wound in lower limb confirmed on physical examination measuring ankle brachial pressure Index(ABPI) were evaluated for ulcer ,cellulitis and gangrene by using WAGNER's classification. Dyslipidemia is assessed in these patient by sending their fasting lipid profile and data is entered into specially designed Performa. Results: We found that majority of cases having abnormal lipid profile. Dyslipidemia with significant difference was found in diabetic foot patients, 54.7% (n=76) patients show HDL <35 ,56.1%(n=77 )have cholesterol >200mg/dl and 69.8%(n=97) have TAG>150mg/dl. 29.5% patient with diabetes have superficial ulcer, while deep ulcer, cellulitis, localized and extensive gangrene was found with percentage of 31.7% , 20.1% ,10.8%, 7.9% respectively . Conclusion: We concluded that Dyslipidemia is a modifiable risk factor for diabetic foot related complications. So diabetic patients must be advised regular Lipid Profile to decrease risk of diabetic foot related complication. Keywords: Diabetes Mellitus (DM), Dyslipidemia, Diabetic foot, PAD and neuropathy